Minor Effect of Antibiotic Pre-treatment on the Engraftment of Donor Microbiota in Fecal Transplantation in Mice - Freitag, Tobias L.; Hartikainen, Anna; Jouhten, Hanne; Sahl, Cecilia; Meri, Seppo; Anttila, Veli-Jukka; Mattila, Eero; Arkkila, Perttu; Jalanka, Jonna; Satokari, Reetta (Frontiers in Microbiology, 2019)
Fecal microbiota transplantation (FMT) is an effective therapy for recurrent Clostridioides difficile infection (rCDI) and is also considered a potential treatment for a wide range of intestinal and systemic diseases. FMT corrects the microbial dysbiosis associated with rCDI, and the engraftment of donor microbiota is likely to play a key role in treatment efficacy. For disease indications other than rCDI, FMT treatment efficacy has been moderate. This may be partly due to stronger resilience of resident host microbiota in patients who do not suffer from rCDI. In rCDI, patients typically have undergone several antibiotic treatments prior to FMT, depleting the microbiota. In this study, we addressed the effect of broad-spectrum antibiotics (Ab) as a pre-treatment to FMT on the engraftment of donor microbiota in recipients. We conducted a pre-clinical study of FMT between two healthy mouse strains, Balb/c as donors and C57BL/6 as recipients, to perform FMT within the same species and to mimic interindividual FMT between human donors and patients. Microbiota composition was assessed with high-throughput 16S rDNA amplicon sequencing. The microbiota of Balb/c and C57BL/6 mice differed significantly, which allowed for the assessment of microbiota transplantation from the donor strain to the recipient. Our results showed that Ab-treatment depleted microbiota in C57BL/6 recipient mice prior to FMT. The diversity of microbiota did not recover spontaneously to baseline levels during 8 weeks after Ab-treatment, but was restored already at 2 weeks in mice receiving FMT. Interestingly, pre-treatment with antibiotics prior to FMT did not increase the overall similarity of the recipient´s microbiota to that of the donor´s, as compared with mice receiving FMT without Ab-treatment. Pre-treatment with Ab improved the establishment of only a few donor-derived taxa, such as Bifidobacterium, in the recipients, thus having a minor effect on the engraftment of donor microbiota in FMT. In conclusion, pre-treatment with broad-spectrum antibiotics did not improve the overall engraftment of donor microbiota, but did improve the engraftment of specific taxa. These results may inform future therapeutic studies of FMT.